Immunotoxin in the Absence of P-Glycoprotein allows Selective Target Cell Killing in the Semi-Direct Antigen Presentation Pathway Following Organ Transplantation. (July 2018) - Meader, Lucy; Brown, Kathryn; Cheung, Lawrence; Smith, Richard; Rosenblum, Michael; Wong, Wilson
Abstract : Introduction: Rejection of transplanted organs by recipient T cells can be via the direct and indirect antigen presentation pathways. Recently, the semi-direct pathway has been highlighted as an important route of antigen recognition. Intact donor antigens are acquired by recipient antigen presenting cells and presented to recipient T cells. This can be via either direct cell to cell contact or exosomes released by donor cells. Strategies to block the semi-direct pathway will no doubt advance the study of this mechanism. We have used an immunotoxin against a single MHC class II molecule expressed by the organ donor that has been transplanted into multidrug resistant (MDR) gene deficient fully allogeneic mouse recipients that are exquisitely sensitive to the toxin. As a result, only recipient cells that have acquired the target donor MHC molecules are killed, providing an in vivo model of the semi-direct pathway of antigen presentation. Materials and Method: The toxin Gelonin was conjugated to mouse anti mouse I-A k antibody (I-A k Gelonin) as previously described (Brown et al. AJT 2016). Donor BL/6 x CBA F1 mice (H-2 b+k ) expressing the target I-A k were given BrdU in their drinking water to label their passenger leukocytes, in order to identify donor cells that had trafficked to recipient spleens by immunohistochemistry. Donor kidneys were transplanted into MDR deficient FVB (H-2 q ) recipients which were injected with I-A k Gelonin immediately after transplantation. Results: Kidneys from BL/6 x CBA F1 mice treated with BrdU were transplanted into MDR -/-, or wild type FVB, recipients with or without I-A k -gelonin. One day after transplant the spleens were harvested for immunohistochemistry. Donor BrdU + cells could be readily detected. Sections were also stained for I-A k expression to quantify BrdU + /I-A k+ (donor passenger leukocytes) and BrdU - /I-A k+ cells (recipient cells that have acquired donor MHC class II molecules, i.e. the target population that takes part in semi-direct antigen presentation). After kidney transplantation into MDR -/- mice, recipient cells that had taken up donor MHC class II (I-Ab + BrdU - cells, the target population) were 18.22+2.71% of the total population. After injection with 0.25 or 0.375mg/kg I-A k -gelonin, this percentage fell to 12.58+4.77% (NS) and 1.08+1.08% ((p=0.0175) respectively, figure below. Preliminary experiments suggest that the immunotoxin has no significant overall effect on graft survival, but has a subtle effect on alloantibody production. Further work is being carried out to elucidate this. Figure. No caption available. Conclusion: Combining the use of an immunotoxin with MDR -/- hosts allows ultra selective depletion of recipient antigen presenting cells in the semi-direct pathway. This technique may help to elucidate the involvement of this pathway in the rejection response.